The molecular and technological characterization of lactic acid bacteria in einkorn sourdough: effect on bread quality - Cakir, Elif; Arici, Muhammet; Durak, Muhammed Zeki; Karasu, Salih (SPRINGER, 2020)
This study aimed to investigate the characterization of lactic acid bacteria strains (LABs) in spontaneous sourdough produced from einkorn flour as a new sourdough source and to determine some quality characteristics of sourdough bread. Thirty-two different LABs were isolated from spontaneously fermented einkorn sourdough under laboratory conditions. Seven different lactic acid bacteria strain (LAB) species, Lb. crustorum (dominant species 10), Pediococcus (4), Lb. brevis (6), Lb. paraplantarum (1), Lb. plantarum (5), Lb. fermentum (4), and Lb. curvatus (2) were identified by PCR (16S). Lb. paraplantarum and P. acidilactici showed high antibacterial activity against B. subtilis ATCC6633, B. cereus ATCC11778, and E. coli ATCC25922, and Lb. crustorum MN047 and L. brevis R-1 showed an antifungal effect on P. carneum, A. flavus, and A. niger. At the same time, all strains showed an acid-tolerant effect, because they showed a survival ratio higher than 70% at pH 2.5. The highest phytase activity was observed from L. paraplantarum 2815 and L. plantarum AAS3. The study aimed to investigate Lb. brevis R-1 and Lb. paraplantarum 7285 starter culture effects and bread quality parameters on dough made solely with einkorn or with a mixture of 25%, 50%, or 75% einkorn flour, compared to a solely wheat flour sourdough. The sourdough bread containing 25% and 50% einkorn flour had better volume, specific volume, and textural properties than bread containing 75% and 100% einkorn flour; they were scored as good as 100% wheat dough bread in terms of sensory properties. This study recommends that einkorn sourdough could be utilized as a beneficial source, having a diverse range of LABs and strong technological properties.
Keywords: Lactic acid bacteria (LAB); PCR; Sourdough; Einkorn bread; IDENTIFICATION; PHYTASE; Food Science & Technology